MAKAN: A low‐cost low‐complexity local positioning system. Issue 2 (21st May 2019) - Kahe, Ghasem; Masoumi Ganjgah, Farhad
Abstract: The vulnerability of global navigation satellite systems (GNSSs) to jamming and unavailability in indoor and dense urban environments in combination with low accuracy for many applications leads to the emergence of various local positioning systems (LPSs). In this paper, we propose an LPS that provides positioning service in the designated area using a set of reference stations employing spread‐spectrum technology. Radio ranging is the basis of radio navigation systems. Design, implementation, and field test of a spread‐spectrum radio ranging system are described. By resolving the synchronization problem using an affordable and available clock source, the complex procedures of acquisition and tracking inside the spread‐spectrum receiver are replaced by a simple acquisition‐only algorithm. Experimental results of the proposed system in the field test are compared with the simultaneously logged GPS data. The experiments demonstrate proof of concept of the proposed system (MAKAN) for GPS‐like performance for positioning in the allocated mission.